Omnibus Law dalam Konstitusi Indonesia: Studi Perbandingan Indonesia, Amerika Serikat, dan Filipina - Rachim, Kania Venisa; Sagala, Christo Sumurung Tua; Mulyono, Eddy (Universitas Serang Raya, 2023)
The Omnibus Law is often discussed and debated, especially in its implementation in Indonesia. Omnibus Law is considered as a solution to make legislation more efficient, Omnibus Law is something new in the formation of legislation in Indonesia. Previously, the Omnibus Law was often used in the common law legal system, and several civil law countries have also implemented the Omnibus Law. In this study, the authors examine the United States and the Philippines. The concept of the Omnibus Law is not only used for one type of law but has penetrated into other sectoral laws. In the Philippines, since 2003 the Omnibus Law has been enacted as a method for forming legislation. It is different from the United States, which has implemented the Omnibus Law since 1850. This research refers to a comparison of the Omnibus Law in the Philippines because the Philippines is a country in the Southeast Asia region just like Indonesia and adheres to a legal system that combines common law and civil law which does not very different from Indonesia, further comparison with the United States Omnibus Law, because the United States is also one of the countries that is the mecca of world law. This study uses normative legal research, using secondary data which is processed using qualitative techniques. This study uses a comparison of two countries which makes this research different from other research related to the Omnibus Law, with the aim of examining the position of the Omnibus Law in Indonesia and making comparisons with the United States and the Philippines.